Exploring the use of Stephen J. Ball’s theoretical tools for the analysis of education policies in Latin America - Beech, Jason; Meo, Analía Inés (Education Policy Analysis Archives, 2016)
In this introductory essay to the special issue on the use of S.J. Ball’s theories in Latin America we explore how Ball’s theoretical concerns and empirical research contributes to visualize, map and problematize some aspects that have been marginalized in most research on education policies in the region. Ball’s contributions are grouped into two main areas. First, the analysis of the participation of new actors in education policy, including businesses and philanthropic organizations; which implies a redefinition of the state and the government of education. The second area we highlight is his work on the policy cycle and his theory of enactment. Ball questions the concept of "implementation" and linear views on the relations between "policy" and "practice." In contrast, he proposes conceptual approaches that contribute to open the black box of educational policies, exploring how they define possible frameworks for action, but at the same time, leave margins for interpretations and actions of individuals acting in different contexts.